The non-medical out-of-pocket costs to attend a free anxiety disorders treatment clinic in Australia. (June 2016) - Anderson, Reece; Wong, Nora; Newby, Jill M; Andrews, Gavin
Objective: Australia has high out-of-pocket costs for medical and non-medical treatments. The 'cost to attend' is seldom added to these estimates. Method: A sequence of 92 participants attending a free Anxiety Disorders Clinic at an inner city public hospital were surveyed about the costs to attend one appointment, including costs such as private /public transport costs and lost income. Results: We found that these out-of-pocket costs were on average AUD$57 per person to attend an appointment at a free point-of-service clinic. Of the 45% who experienced financial burden from attending, the majority reported only slight burden. Conclusion: This level of 'cost to attend' a free outpatient treatment clinic is non-trivial given people with anxiety and depressive disorders, like many others with chronic disorders, will need at least 6–10 visits to complete a course of treatment.